KORELACJA WAD OŚWIADCZENIA WOLI PRZY ZAWARCIU MAŁŻEŃSTWA NA GRUNCIE PRAWA KANONICZNEGO I POLSKIEGO - Pielichowski, Jerzy (Zeszyty Prawnicze, 2016)
CORRELATION OF DEFECTS OF DECLARATION OF INTENT WHEN ENTERING INTO MATRIMONY UNDER CANON LAW CODE AND FAMILY AND GUARDIANSHIP CODE Summary The analysis concerns the intertwining of the areas of secular and canon law with regard to defects of a declaration of will at the time of contracting a marriage. The author proceeds from an analysis of the historic background to denominational marriages starting with the 1557 Synod of Piotrków, until the 1917 enactment of the Canon Law Code (Kodeks Prawa Kanonicznego, „KPK”), when a uniform approach to marriage was adopted in the whole Universal Church. He goes on to look into the question of the forms of contracting a marriage, both the ordinary and the extraordinary form, based on the provisions of the Canon Law Code from 1983. A further part of the analysis looks back at the historical evolution of the regulations relating to the defects of the declaration of will in Polish matrimonial legislation, with emphasis on the periods when Poland was partitioned by the neighboring powers and on post-WWII Polish and international legislation relating to family matters. The article ends with an analysis of the defects of declarations of intent made in connection with entering into matrimony under the KPK and under the Family and Guardianship Code („KRO”). Under the former, these include: the lack of sufficient use of reason, significant absence of the person’s awareness of material marital rights and duties, mental inability to accept significant marital duties, error, trickery, simulation of marital consent, conditional consent, coercion or fear, while under KRO these would include: lack of awareness of a declaration of will, mistake concerning a person and threat.